FORMATION OF CADETS ' READINESS FOR INTERPERSONAL COMMUNICATION IN THE PROCESS OF INCLUSION IN EXTRACURRICULAR ACTIVITIES OF THE UNIVERSITY - T. G. Mukhina; N. I. Musina (Вестник Мининского университета, 2020)
Introduction. Interpersonal communication in police activities is an urgent problem, since the police is obliged to provide practical assistance to everyone who needs it, interaction and cooperation is positioned as a principle of the police. Showing tact in solving law enforcement tasks, the ability to mitigate conflict manifestations and take into account the range of interests of social partners when resolving legal conflicts, etc. play a role in improving the efficiency of operational activities. It is important in the educational process of the University to form a readiness for interpersonal communication using the potential of extracurricular activities, which can make a significant contribution to the formation of the personality of the future police officer. Materials and methods. As a result of the study and analysis of scientific literature, the experience of organizing extracurricular activities of cadets, the following areas were identified that focus on the inclusion of cadets in interpersonal communication (industrial practice, scientific extracurricular activities, professional and moral education and cultural development, physical culture and recreational activities). Each direction is characterized by leading forms, methods, and conditions. In order to determine the effectiveness of the work carried out, diagnostic tools have been developed. The diagnostic tools included the questionnaire of interpersonal relations of A. A. Rukavishnikov (OMO) and the methodology of E. A. Rukavishnikov. Bogardus "Scale of social distance". These methods allowed us to evaluate typical ways of students ' attitude to people and determine the degree of social and psychological acceptance of each other by people. The experimental group (EG) made up of 124 student AT Ministry of the interior (G. N. Novgorod), and VA MVD Rossii (Volgograd), control group (CG) 119 cadets of the Ministry of internal Affairs of Russia (G. N. Novgorod), and VA MVD Rossii (Volgograd).Results of the study. The results of the experiment confirmed the positive impact of systematic organized extracurricular activities on the formation of readiness of future police officers forinterpersonal communication. Discussion and conclusions. Thus, during the experimental work, the authors paid special attention to interpersonal communication as a global human value. Comprehensive integration ofextracurricular activities and activation of life activities of future specialists of the Ministry of internal Affairs of Russia in the following areas: industrial practice, scientific extracurricular activities, professional and moral education and cultural development, physical culture and recreational activities allowed changing the content of the educational environment of the University. At the same time, the coordination and control functions for organizing purposeful systematic unification of all areas of extracurricular work, including integration with classroom activities, are assigned to the teaching staff, teachers-curators of training groups, and the course link.